Productive development policies in Latin American countries: The case of Peru, 1990 - 2007 - Mario D. Tello; José Tavara (Inter-American Development Bank (IDB), 2010)
This paper assesses the institutional setting and productive impact of selected productive development policies (PDPs), institutions, and programs implemented in Peru during the period 1990-2007. The assessment is based on a simple, basic framework of a series of economic or market failures that may have constrained the transformation of the productive structure, the process of innovation, and the growth of total factor productivity. Evidence indicates that the PDPs and structural reforms implemented in Peru did not significantly alter the productive structure of the Peruvian economy. If the objectives of the PDPs are to transform the productive structure, increase total factor productivity, and enhance innovation, government interventions need to focus directly on the source of market failures and create quality productive changes within the private sector.
hdl:11319/1499
Keywords: L50; O25; O40; 330; Productivity; Industrial policy; Innovation; Peru